2006
DOI: 10.1111/j.1463-6409.2006.00222.x
|View full text |Cite
|
Sign up to set email alerts
|

Status of two cryptic species, Typhlodromus exhilaratus Ragusa and Typhlodromus phialatus Athias‐Henriot (Acari: Phytoseiidae): consequences for taxonomy

Abstract: Status of two cryptic species, Typhlodromus exhilaratus Ragusa and Typhlodromus phialatus Athias-Henriot (Acari: Phytoseiidae): consequences for taxonomy -Zoologica Scripta, 35, 115-122. Typhlodromus phialatus and T. exhilaratus are morphologically close species. Their differentiation is based on the shape of the insemination apparatus and on idiosomal setae length. However, the setae length values are often intermediate between these two species and do not allow accurate identification. Furthermore, the handf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
49
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 27 publications
4
49
1
Order By: Relevance
“…Phytoseiids are found both in cultivated plots and in their neighbouring uncultivated areas. In a study conducted in vineyards of the South of France, two morphologically close species (only distinguishable by the shape of their spermatheca; Tixier et al 2006a) have been reported to occur in diVerent habitats of the agroecosystem ( Barbar et al 2005;Tixier et al 2006b). While Typhlodromus exhilaratus Ragusa was the prevailing species in vine plots, Typhlodromus phialatus Athias-Henriot was predominant in neighbouring uncultivated areas, especially on Viburnum tinus L. Trap catches showed that T. phialatus could migrate into the vine Weld, but it never reached densities as high as for T. exhilaratus (Tixier et al 2006b).…”
Section: Introductionmentioning
confidence: 98%
“…Phytoseiids are found both in cultivated plots and in their neighbouring uncultivated areas. In a study conducted in vineyards of the South of France, two morphologically close species (only distinguishable by the shape of their spermatheca; Tixier et al 2006a) have been reported to occur in diVerent habitats of the agroecosystem ( Barbar et al 2005;Tixier et al 2006b). While Typhlodromus exhilaratus Ragusa was the prevailing species in vine plots, Typhlodromus phialatus Athias-Henriot was predominant in neighbouring uncultivated areas, especially on Viburnum tinus L. Trap catches showed that T. phialatus could migrate into the vine Weld, but it never reached densities as high as for T. exhilaratus (Tixier et al 2006b).…”
Section: Introductionmentioning
confidence: 98%
“…Taken together, there are clear indications that the three N. paspalivorus geographic populations are biologically different despite their morphological similarity. Such biological differences between morphologically similar populations may indicate cryptic species (Muma and Denmark 1969;Monetti and Croft 1997, Tixier et al 2003, 2006a. To test whether the three allopatric populations are "potentially able to interbreed and produce viable progeny" (Biological species sensu Mayr 1940) is necessary to understand the evident biological differences between the three geographic populations.…”
Section: Introductionmentioning
confidence: 99%
“…The phytoseiid species inhabiting vineyards usually belong to the predatory type III as defined by McMurtry and Croft (1997): generalist predators able to consume pest mite, but also to feed and develop on other food sources such as pollen, exudates or insect larvae when the preferential preys are absent. The natural occurrence of these species on uncultivated plants around crops is often reported (Boller et al 1988;Tuovinen and Rokx 1991;Valentin and Kreiter 1993;Tuovinen 1994;Kreiter et al 2000Kreiter et al , 2002Tixier et al 2000aTixier et al , b, 2006aMoraes et al 2004; Barbar et al 2005). In addition, several studies have focused on the impact of the presence of herbaceous and flowering plants (wild or cultivated) in and out the crops on phytoseiid mite communities (Flaherty 1969;Boller et al 1988;Liguori and Castagnoli 1989;Coli et al 1994;Tsolakis et al 1997;Castagnoli et al 1999;Kreiter et al 2000Kreiter et al , 2002Tixier et al 2000aTixier et al , b, 2006aNicholls et al 2001;Duso et al 2004;Mailloux et al 2010).…”
Section: Introductionmentioning
confidence: 93%
“…The natural occurrence of these species on uncultivated plants around crops is often reported (Boller et al 1988;Tuovinen and Rokx 1991;Valentin and Kreiter 1993;Tuovinen 1994;Kreiter et al 2000Kreiter et al , 2002Tixier et al 2000aTixier et al , b, 2006aMoraes et al 2004; Barbar et al 2005). In addition, several studies have focused on the impact of the presence of herbaceous and flowering plants (wild or cultivated) in and out the crops on phytoseiid mite communities (Flaherty 1969;Boller et al 1988;Liguori and Castagnoli 1989;Coli et al 1994;Tsolakis et al 1997;Castagnoli et al 1999;Kreiter et al 2000Kreiter et al , 2002Tixier et al 2000aTixier et al , b, 2006aNicholls et al 2001;Duso et al 2004;Mailloux et al 2010). However, only few studies dealt with the effect of agroforestry management (trees and/or shrubs combined with crops) on communities of natural enemies and consequently on pest management (Altieri and Letourneau 1982;Linit and Stamps 1995;Altieri and Nicholls 2002).…”
Section: Introductionmentioning
confidence: 93%